Optimalisasi Alokasi Dana Desa dalam Peningkatan Perekonomian Masyarakat di Nagari Bomas Solok Selatan - Dwi Putra Ayri, Dicky; Jumiati, Jumiati; Saputra, Boni (PUBLICNESS: Journal of Public Administration Studies, 2025)
Economic disparities between urban and rural areas in Indonesia create structural challenges to equitable national development. At the same time, the optimization of Village Funds still faces gaps between theoretical potential and practical realization despite more than a decade of implementation. This study aims to comprehensively analyze the optimization of Village Fund Allocation in improving community economy in Nagari Bomas, Sungai Pagu District, South Solok Regency. The research methodology employed a qualitative approach with an instrumental case study design involving 10 key informants selected through purposive sampling. Methodological triangulation was implemented through in-depth interviews, participatory observation over six months, and the analysis of 45 official documents using inductive thematic analysis techniques. Research findings demonstrate a strategic evolution from a focus on physical infrastructure toward a holistic approach that integrates physical and non-physical development, with BUMNag's "Tungku Tigo Sajarang" catalyzing economic diversification, creating employment opportunities, and enhancing Village Original Income. This study contributes to the development of a multidimensional analytical framework that integrates governance, economic growth, and local institutional capacity perspectives within the context of the nagari governance system while providing empirical evidence that the effectiveness of the Village Fund depends on the quality of participatory planning processes, local institutional capacity, and economic diversification strategies based on village resource potential.